Early respiratory impairment and pneumonia after hybrid laparoscopically assisted esophagectomy: a comparison with the open approach - Reichert, Martin; Lang, Maike; Hecker, Matthias; Schneck, Emmanuel; Sander, Michael; Uhle, Florian; Weigand, Markus A.; Askevold, Ingolf; Padberg, Winfried; Grau, Veronika; Hecker, Andreas (Journal of Clinical Medicine, 2020)
Patients undergoing esophageal cancer surgery are at high risk of developing severe pulmonary complications. Beneficial effects of minimally invasive esophagectomy had been discussed recently, but the incidence of perioperative respiratory impairment remains unclear. This is a retrospective single-center cohort study of patients, who underwent open (OE) or laparoscopically assisted, hybrid minimally invasive abdomino-thoracic esophagectomy (LAE) for cancer regarding respiratory impairment (PaO2/FiO2 ratio (P/FR) < 300 mmHg) and pneumonia. No differences were observed in the cumulative incidence of reduced P/FR between OE and LAE patients. Of note, until postoperative day (POD) 2, P/FR did not differ among both groups. Thereafter, the rate of patients with respiratory impairment was higher after OE on POD 3, 5, and 10 (p ≤ 0.05) and tended being higher on POD 7 and 9 (p ≤ 0.1). Although the duration of LAE procedure was slightly longer (total: p = 0.07, thoracic part: p = 0.004), the duration of surgery (Spearman’s rank correlation coefficient (rsp) = −0.267, p = 0.006), especially of laparotomy (rsp = −0.242, p = 0.01) correlated inversely with respiratory impairment on POD 3 after OE. Pneumonia occurred on POD 5 (1–25) and 8.5 (3–14) after OE and LAE, respectively, with the highest incidence after OE (p = 0.01). In conclusion, respiratory impairment and pulmonary complications occur frequently after esophagectomy. Although early respiratory impairment is independent of the surgical approach, postoperative pneumonia rate is reduced after LAE.